Pengujian dalam Pengambilan Keputusan Investasi Menggunakan Model Belief Adjustment dengan Pola Penyajian End of Sequence - Arvianti, Vivi Septi; Sari, Rida Perwita (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to examine whether the End of Sequence presentation pattern has an influence on investment decision making using the order of evidence (good news followed by bad news and bad news followed by good news), non-complex information type (fundamental analysis) and complex information type (fundamental analysis and technical analysis). This experimental research uses a 2 x 2 factorial experimental design between designs with variables that manipulate independent variables, namely the order of information evidence and information type, and investment decisions as the dependent variable. This study used students of the Bachelor of Accounting study program at UPN "Veteran" East Java as research subjects with a total of 82 students who have met the requirements, namely being / having taken the Financial Statement Analysis and Investment Management courses. This study uses normality test and Kruskall Wallis test. The results of this study are the effect in making investment decisions using the End of Sequence presentation pattern in a long series of information shows that non-complex information (fundamental analysis) can cause no order effect, but when presented using complex information (fundamental analysis and technical analysis) shows recency effect.